Herpes Simplex Virus Type 2 Vaccines: New Ground for Optimism? - Aurelian, L. (American Society for Microbiology, 2004)
The development of effective prophylactic and therapeutic vaccines against genital herpes has proven problematic. Difficulties are associated with the complexity of the virus life cycle (latency) and our relatively poor understanding of the mechanism of immune control of primary and recurrent disease. The types of effector cells and the mechanisms responsible for their activation and regulation are particularly important. Studies from my and other laboratories have shown that recurrent disease is prevented by virus-specific T helper 1 (Th1) cytokines (viz., gamma interferon) and activated innate immunity. Th2 cytokines (viz., interleukin-10 [IL-10]) and regulatory (suppressor) T cells downregulate this immune profile, thereby allowing unimpeded replication of reactivated virus and recurrent disease. Accordingly, an effective therapeutic vaccine must induce Th1 immunity and be defective in Th2 cytokine production, at least IL-10. These concepts are consistent with the findings of the most recent clinical trials, which indicate that (i) a herpes simplex virus type 2 (HSV-2) glycoprotein D (gD-2) vaccine formulated with a Th1-inducing adjuvant has prophylactic activity in HSV-2- and HSV-1-seronegative females, an activity attributed to the adjuvant function, and (ii) a growth-defective HSV-2 mutant (ICP10ΔPK), which is deleted in the Th2-polarizing gene ICP10PK, induces Th1 immunity and has therapeutic activity in both genders. The ICP10ΔPK vaccine prevents recurrent disease in 44% of treated subjects and reduces the frequency and severity of recurrences in the subjects that are not fully protected. Additional studies to evaluate these vaccines are warranted.